Peran Guru PAI dalam Menerapkan Metode Pembelajaran Berbasis Pembiasaan untuk Mengembangkan Karakter Religius dan Disiplin Peserta Didik - Triyono, Agus; Subando, Joko (TSAQOFAH, 2026)
Instruction in Islamic Religious Education (PAI) plays a strategic role in shaping students’ personalities to be faithful, pious, morally upright, and disciplined in everyday life, thereby requiring effective methods to internalize these values from the Madrasah Ibtidaiyah level. This study aimed to describe the role of PAI teachers in implementing a habituation-based learning method to develop students’ religious and disciplinary character in Madrasah Ibtidaiyah. The research employed a qualitative approach with a descriptive design, with data collected through observation, interviews, and documentation. The findings show that PAI teachers act as designers of habituation programs, implementers and mentors of religious activities, behavioral role models, supervisors and evaluators, and reinforcers of character values. The forms of habituation applied include the habituation of worship, moral conduct, discipline, and responsibility. Consistent implementation of the habituation method was found to strengthen students’ religious and disciplinary character, as reflected in increased awareness of worship, adherence to rules, politeness, honesty, and responsibility. The study concludes that a habituation-based learning method supported by the active role of PAI teachers is an effective strategy for developing students’ religious and disciplinary character in Madrasah Ibtidaiyah, and underscores the importance of reinforcing the teacher’s role as a model and primary driving force in value-based character education.